Jener W. Nielson, Charter and Ordinances of the City of Fresno, California 52 (1916) - (:unkn) unknown (My University, 1891)
No. 221, § 8: Prohibited the concealed carry of any pistol, firearm, slungshot, dirk, Bowie-knife, or other deadly weapon without written permission from the President of the Board of Trustees while within city limits. Violators guilty of a misdemeanor.
Keywords: CARRY - CONCEALED